QTL Mapping and Heterosis Analysis for Fiber Quality Traits Across Multiple Genetic Populations and Environments in Upland Cotton - Li, Cong; Yu, Hurong; Li, Cheng; Zhao, Tianlun; Dong, Yating; Deng, Xiaolei; Hu, Jiahui; Zhang, Yi; Zhang, Fan; Daud, M. K.; Chen, Jinhong; Zhu, Shuijin (Frontiers in Plant Science, 2018)
An “immortalized F2” (IF2) and two reciprocal backcross (HSBCF1 and MARBCF1) populations were constructed to investigate the genetic bases of fiber quality traits in upland cotton across four different environments. A relatively high level of heterosis for micronaire (MIC) in IF2s, as well as fiber length (FL) and MIC in MARBCF1s was observed. A total of 167 quantitative trait loci (QTLs) was detected in the three related experimental populations and their corresponding mid-parental heterosis (MPH) datasets using the composite interval mapping (CIM) approach. Analysis of genetic effects of QTLs detected in different populations and their MPH datasets showed 16 (24.24%) partial dominance (PD) QTLs and 46 (69.70%) over-dominance (OD) QTLs were identified in an IF2 population; 89 (62.68%) additive QTLs, three (2.11%) PD QTLs, and 49 (34.51%) OD QTLs were detected in two BCF1 populations. Multi-environment analysis showed 48 and 56 main-QTLs (m-QTLs), and 132 and 182 epistasis-QTLs (e-QTLs), by inclusive composite interval mapping (ICIM) in IF2 and two BCF1 populations, respectively. Phenotypic variance explained by e-QTLs, except for MARBCF1s, was higher than that by m-QTLs. Thus, the over-dominant, partial dominant, and epistasis effects were the main causes of heterosis in the IF2 population, while the additive, over-dominant, and epistasis effects were the primary genetic basis of heterosis in the two BCF1 populations. Taken together, additive effect, partial dominance, over-dominance, and epistasis contributed to fiber quality heterosis in upland cotton, but over-dominance and epistasis were the most important factors.